O papel da mulher como mulher no papel : representações femininas em anúncios de jornais impressos sergipanos - Reis, Ana Alinny Cruz (2018)
Advertising as cultural production is influential in the role of women in society, supporting social, cultural and aesthetic standards of acceptable female behaviour. Starting from this premise, on the basis of Cultural and Gender Studies - Hall (2003, 2005), Woodward (2007), Silva (2009) Kellner (2001), Butler (2003) and Buitoni (1981), among others – we seek to observe how the discourses in which women are placed at the centre of the advertising campaign happen, in a comparative perspective, from classified advertisements inserted in the main newspapers of the State. The research is divided in two complementary stages, the bibliographical and documentary stage and the empirical one, indispensable in order for the intended purpose to be fulfilled. The methodological approach is the Content Analysis proposed by Laurence Bardin (2009). The corpus of the research is composed byads printed in newspapers of circulation in Sergipe, from 1948 to 2015, carefully selected from the collection of the Historical and Geographical Institute of Sergipe. As expected results of the analysis, we seek to identify aspects and characteristics that emerge from women's exposure in classified advertisements, and whether this advertisement is a portrait of the culture in which women are embedded and if it reflects the cultural and ideological values in vogue.